Searching for Dual Inhibitors of the MDM2‐p53 and MDMX‐p53 Protein–Protein Interaction by a Scaffold‐Hopping Approach. (19th December 2014) - Zaytsev, Andrey; Dodd, Barry; Magnani, Matteo; Ghiron, Chiara; Golding, Bernard T.; Griffin, Roger J.; Liu, Junfeng; Lu, Xiaohong; Micco, Iolanda; Newell, David R.; Padova, Alessandro; Robertson, Graeme; et al.
<x xml:space="preserve">Abstract</x> Two libraries of substituted benzimidazoles were designed using a 'scaffold‐hopping' approach based on reported MDM2‐p53 inhibitors. Substituents were chosen following library enumeration and docking into an MDM2 X‐ray structure. Benzimidazole libraries were prepared using an efficient solution‐phase approach and screened for inhibition of the MDM2‐p53 and MDMX‐p53 protein–protein interactions. Key examples showed inhibitory activity against both targets.